EPISTEMOLOGI KEPEMIMPINAN TRANSFORMASIONAL DAN NILAI-NILAI TRADISIONAL KIAI DALAM MEMBENTUK KARAKTER SANTRI DI ERA DIGITAL: STUDI KASUS PONDOK PESANTREN NURUL HARAMAIN ALMALIKI - Maizah, St.; Ahmad Barizi (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to examine the epistemology of transformational leadership integrated with the traditional values of Islamic scholars in shaping the character of students in the digital era, using a case study at the Nurul Haramain Almaliki Islamic Boarding School in Karangploso, Malang. A qualitative approach is used to explore how Kiyai Hasan Basri actualizes a transformational leadership style—which emphasizes vision, exemplary behavior, motivation, and individual attention—in the context of Islamic boarding school education, which is rich in Islamic traditional values. The results show that Kiyai Hasan's leadership successfully shapes the character of students through a combination of spiritual and strategic approaches that balance adab, discipline, and awareness of changing times. While maintaining classical learning methods such as sorogan and bandongan, this Islamic boarding school gradually opens up space for digital literacy without eliminating Islamic moral and ethical values. This integration is evidence that tradition and transformation can go hand in hand in shaping students who are virtuous, independent, and adaptive to the digital era. Thus, the epistemology of transformational leadership framed by the traditional values of Islamic boarding schools becomes a strong foundation in the character education of today's Islamic boarding school students. Keyword: Epistemology, Transformational Leadership, Traditional Kiyai Values, Character Education, Digital Era